GAYA BAHASA DALAM PENGGALAN NOVEL PUDARNYA PESONA CLEOPATRA KARYA HABIBURRAHMAN EL-ZHIRAZY - Qurratul A’ini (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2017)
This literary work analyzes the novel by Habiburrahman El-zhirazy entitled "Clearing the Fade of Cleopatra" that tells a figure who was obsessed with the beauty of Egyptian women. The desire was vanished because the character was mated by her parents. Using a stylistic approach, this study examined how dictions and the existing majesties in the novel fragments were applied. The source of data was a fragment of the novel "Clearing the Fade of Cleopatra", and the data were the lingual units in terms of words, phrases, clauses and sentences that contained thf figurative languages. The study revealed that in selecting the dictions the writer used Arabic, English and Javanese. The selection of diction is certainly not separated from the author's background. The figurative language included hyperbole, metaphor, paradox, allegory and personification. The  hyperbolic was used more frequently than other figurative  languages.